Description of Tenun Songket Lansek Manih Training Strategies in IRA Songket, Sijunjung - Nori Diana Putri; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
This research is motivated by the success phenomenon of Tenun Songket Lansek Manih Training Strategies in IRA Songket, Sijunjung. This is evidenced by the presence, liveliness, and achievements obtained by the residents learning from the work of songket weaving. Researchers suspect the cause of the successful implementation of songket weaving training because of the learning strategies used by the instructor in interesting training. This type of research is quantitative descriptive research. The population in this study were 70 people who studied at IRA Songket. The sampling technique used is simple rendom sampling. Samples were taken as 35 people. While the questionnaire guidelines data collection tool. Data analysis techniques use a percentage formula. The results showed that Songket Lansek Manih Weaving Training Learning Strategy in Sijunjung IRA Songket from the aspects of learning methods, learning media, and learning resources was categorized as good.Keywords:Methods, Media, Learning Resources